(untitled) (Revista de Ciências Agroveterinárias, 2012)
Considering the benefits of a well-planned urban forest, it should also be valued in school areas. To this end, toxic and allergenic species, as well those with traits that have the potential to cause accidents (e.g. thorns or pointed leaves) should not be used. In addition, the use of exotic species should also be avoided as they do not contribute to the knowledge of regional flora and can bhave an invasive habit in natural areas. Thus, the purposes of this study were to study the trees in state schools of the municipality of Lages, SC, and to detect problems with regard to accident risks and the excessive use of exotic species. To this end, nine state schools (34.61%) from a total of 26 present in the urban area were sampled. In each sample group, all tree individuals were identified, quantified and evaluated with regard their risk to people, and classified as native or exotic. A total of 134 trees were recorded, with 76.87% of them presenting some type of toxicity, allergenic components and risk to people and 57.46% belonging to exotic species. The results show a need for a rethinking of the arborisation found in state schools of Lages, with the choice of adequate species which present no risk to people and are native of the region, such as Handroanthus albus (Cham.) Mattos and Eugenia uniflora L.